The Effectiveness of the Use of Assistive Technology Malitung for Learning Outcomes of Students with Mild Intellectual Disabilities (Department of Mathematics, Universitas Negeri Semarang, 2023)
The purposes of this research were to test the effectiveness of the use of assistive technology malitung (manik, tali, hitung) for learning outcomes of students with mild intellectual disabilities in basic arithmetic operations topic and describe their learning outcomes when using assistive technology malitung at Ungaran Public Special School. The method used in this research was Single Subject Research (SSR) with A-B-A design followed by qualitative descriptive research. Data collection techniques used in this research were observation, interviews, questionnaires, and tests. The data analysis techniques used in this research were descriptive statistics, data reduction, data presentation, data interpretation, and conclusion drawing. There were 3 students as research subjects who were students of class IX-C at Ungaran Public Special School. The results of this study are that the learning outcomes of the three research subjects in terms of cognitive, affective, and psychomotor aspects increased and reached category pretty good, good, and very good categories in learning using assistive technology malitung. These results were reinforced by very positive responses from Research Subjects 1 and 3 and positive responses from Research Subjects 2. The conclusions obtained were 1) the use of assistive technology malitung effective on the learning outcomes of students with mild intellectual disabilities on basic arithmetic operations material at Ungaran Public Special School, 2) basic arithmetic operations ability, curiosity, accuracy, responsibility, never give up, enthusiasm for learning, confidence, and interest in learning, problem-solving skills related to addition, subtraction, multiplication, and division operations were achieved in pretty good, good, and very good categories in learning by using assistive technology malitung.